Agronomic performance of 4n x 2nderived plantain (Musa sp. AAB group) hybrids in a humid agroecological zone of Nigeria - Shaibu, A.A.; Nwonuala, A.I.; Tenkouano, A.; Ogburia, M.N. (African Journals Online, 2003)
A field experiment was conducted on thirteen (13) Musa hybrids derived from 4n x 2n crosses, three (3) checks and two (2) plantain landraces to evaluate phenology, growth characteristics and yield performance in a humid agro ecological zone of Nigeria. Fifteen (15) phenotypic characters were significantly different (P<0.01) for phenology and yield performance among the Musa genotypes studied. All hybrids were shorter than the plantain land races. Hybrid 25344-18 (secondary triploid) derived from 7152-2 x 9128-3 had significantly heavier bunch weight (20.5 kg) than the other hybrids and controls. Yield component analysis revealed that bunch weight largely depended on large fruit, number of hands, fruit length and fruit length and fruit circumference. The index of not spotted leaf was not statistically significant for all the genotypes evaluated.